Diversity in Fruit Morphology and Nutritional Composition of Juglans mandshurica Maxim in Northeast China - Li, Zhixin; Wang, Weihuai; Zhang, Haixiao; Liu, Jinhong; Shi, Baoying; Dai, Weizhao; Liu, Kewu; Zhang, Hanguo (Frontiers in Plant Science, 2022)
Although Manchurian walnut (Juglans mandshurica Maxim) is widely distributed in northeast China, very few studies had been reported on its diversity among different populations. We surveyed 12 J. mandshurica populations in their native habitats across the northeast region of China and profiled 13 fruit morphological traits. We found a large degree of variations for these traits, especially for fruit weight (coefficient of variation, or CV of 22.00%), nut weight (CV of 19.42%), and kernel weight (CV of 19.89%). Statistical analysis showed that a large portion of the total variation can be attributed to within-population variation (66.64%), followed by random error (20.96%). We also comprehensively quantified the nutritional composition including fatty acids, amino acids, vitamins, and micronutrients. Similar to fruit morphological traits, we found large variation for most kernel components, which mostly can be explained by within-population variation. Further correlation analysis revealed the dependence of some morphological and nutritional traits on key geographical and ecological factors such as latitude, accumulated temperature, and day length. For instance, a significant positive correlation was found between fruit dimensions and equivalent latitude and precipitation, indicating that such factors should be considered for breeding. Taken together, our data provided a rich dataset for characterizing the variation among J. mandshurica populations and a foundation for selective breeding.